Particuliere archieven 3.0. Uitdagingen van het digitale heden - Jeurgens, Charles (Studies over de sociaaleconomische geschiedenis van Limburg, 2021)
Abstract Archival policy is facing new operational issues and questions. The digital turn has not only changed the ways in which data and information are created, used and stored, but is also confronting archivists with new challenges in building relationships with the creators of records. For ‘private’ archives (keeping materials of companies, organizations and individuals, such as SHCL) the challenge is even bigger, as they need to engage with the online platforms and network communities that have emerged in contemporary society. Surprisingly, this engagement breathes new life into archival policies as it was discussed around 1900, when the idea of ‘community’ as creator of archives was introduced.